2022
DOI: 10.1371/journal.pone.0279015
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in borderline personality disorder: A scoping review

Abstract: Borderline Personality Disorder (BPD) is often perceived to be a female-predominant disorder in both research and clinical contexts. Although there is growing recognition of possible sex differences, the current literature remains fragmented and inconclusive. This scoping review aimed to synthesize available research evidence on potential sex differences in BPD. PsycINFO, PubMed, Scopus and Web-of-Science were searched from January 1982 to July 2022 surrounding the key concepts of sex and BPD. Data searching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 147 publications
(106 reference statements)
0
5
0
1
Order By: Relevance
“…A review on gender differences in borderline personality disorder has been recently published (2) and deserves a comparison between its results and our findings. While conclusions concerning symptoms and comorbid disorders, developmental and biological factors, and treatment issues are mainly concordant in the two studies, our review contains a detailed examination of differences concerning prevalence of BPD and more common diagnostic criteria endorsed by male and female patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A review on gender differences in borderline personality disorder has been recently published (2) and deserves a comparison between its results and our findings. While conclusions concerning symptoms and comorbid disorders, developmental and biological factors, and treatment issues are mainly concordant in the two studies, our review contains a detailed examination of differences concerning prevalence of BPD and more common diagnostic criteria endorsed by male and female patients.…”
Section: Discussionmentioning
confidence: 57%
“…These psychopathological features are exhibited in both genders, but whether they are more common for men or women is still debated in the literature and remains an open empirical question. Studies that specifically investigated clinical differences among gender in BPD patients are still limited (2). Some of these indicated that certain BPD features are more commonly found in women (3)(4)(5)(6)(7)(8)(9) others showed no significant difference across gender (10)(11)(12)(13) and the minority of them reported that some clinical manifestations are more common in men (3,6,14).…”
Section: Introductionmentioning
confidence: 99%
“…La asociación entre el sexo y el TPL coincide con lo hallado en la mayoría de los estudios epidemiológicos, revelando una mayor incidencia de este trastorno en mujeres que en hombres. Nuestros resultados son similares a los reportados por investigaciones como las de Sansone et al ( 16) y Qian et al (17), que identificaron una predominancia de mujeres con TPL, tanto en poblaciones clínicas como no clínicas. Sin embargo, esta disparidad podría verse afectada por aspectos culturales o de género, que podrían influir en la manifestación o detección del TPL.…”
Section: Discussionunclassified
“…Finally, a meta-regression was performed (Mod; p < .05; R 2 > .5) based on a mixed effects model and maximum likelihood method aiming to examine the effect of variables that theoretically may be influencing the relationship between ERP and BPD symptoms. Indicators of exposed groups such as the female ratio (percentage of women in the sample), inequality index (Gini of the country) and gross domestic product (GDP of the country) were chosen as it has been shown that socioeconomic status and inequality are frequently linked to mental health issues (Harnett et al, 2023 ; O’Donoghue et al, 2023 ; Winsper et al, 2020 ), and mixed results have been reported on the gender-based prevalence of BPD across populations (Arranz et al, 2021 ; Qian et al, 2022 ; Sansone & Sansone, 2011 ). Thus, we hypothesize that these variables could potentially moderate the link between ERP and BPD symptoms.…”
Section: Methodsmentioning
confidence: 99%